Formação de padrões em sistemas complexos - Robson Luiz Santos (2004)
In this work an experimental study of a pattern forming system was performed and analyzed. A general approach to properties of pattern formation is presented based on a non-equilibrium thermodynamic model, following results found in the literature. We present results of the experiment performed observing the destabilization of a °uid-°uid interface under a viscous °ow. Image processing techniques allowed us to obtain measurements of relevant interface information in order to capture the pattern dynamics. This way pattern growth rate dispersion curve was measured and found to be in good agreement with the theoretical model, in a region close to the bifurcation. Full qualitative agreement was obtained in the whole range of °ow conditions used.Analysis of the mean interface position also delivered important information, and showed a critical behavior at the bifurcation. This opens the possibility of future observations concerning precursor dynamics in this system.